Från tystnadsplikt till rapporteringsskyldighet – hur yrkesrollen avgör rapporteringsskyldigheten - Lindqvist,Hanna (2024)
With globalization, it has become increasingly easy for companies to shift profits, leading to the erosion of member states’ tax bases. To counter this development, the OECD has long worked on the BEPS (Base Erosion and Profit Shifting) project. One key measure introduced under the BEPS project is the implementation of mandatory disclosure rules. Inspired by the OECD, the European Union adopted the DAC 6 directive, which Sweden has implemented through the Swedish Act (2020:434) on Reportable Arrangements, as well as by introducing a new chapter in the Swedish Tax Procedure Act (2011:1244). The regulations require advisors to disclose certain cross-border arrangements to the Swedish Tax Agency, providing authorities with enhanced capabilities to identify harmful tax schemes. Lawyers are exempt from disclosure obligations when bound by professional privilege, but in such cases, they must inform their clients that the disclosure obligation transfers to them. In contrast, authorized tax advisors affiliated with FAR are not exempt from disclosure obligations, despite also being bound by professional privilege rules. This thesis investigates the circumstances under which lawyers are not protected by professional privilege and are therefore subject to the same disclosure obligations as authorized tax advisors. The study reveals that clients can waive professional privilege, which consequently renders lawyers obligated to disclosure. The analysis further highlights that lawyers may have disclosure obligations concerning marketable arrangements. Additionally, arguments are presented suggesting that lawyers, like authorized tax advisors, should assess on case-by-case basis whether an arrangement is disclosable before informing their clients. When lawyers and authorized tax advisors have differing obligations, the thesis explores whether the law should be amended based on a maxim of equal treatment. This maxim states that similar cases should be treated alike, while different cases should be treated differently. To address this question, the thesis compares lawyers and authorized tax advisors based on their respective organizations – the Swedish Bar Association and FAR – as well as their roles, oversight mechanisms, educational requirements and professional privilege. The analysis reveals that lawyers have a statutory professional privilege, dual oversight mechanisms, and a quality assurance, distinguishing them from authorized tax advisors. At the same time, they often perform identical tasks in practice, and their educational requirements and ethical guidelines are, in many respects, similar. In conclusion, the thesis finds that there is no definitive answer to whether the law should be amended to equalize the obligations of lawyers and authorized tax advisors. Instead, the thesis presents arguments both for and against legislative amendments, focusing on considerations such as legal certainty, transparency, and the unique societal role of lawyers.
Keywords: skatterätt; social and welfare law; rapporteringsskyldighet; rapporteringsplikt; DAC 6; advokat; FAR; Advokatsamfundet; auktoriserad skatterådgivare; RAL; likabehandling